Kinesin family member 2C promotes hepatocellular carcinoma growth and metastasis via activating MEK/ERK pathway. Issue 11 (7th September 2021) - Ding, Qian; Jiang, Caihua; Zhou, Yajing; Duan, Jianping; Lai, Jianming; Jiang, Min; Lin, Dongdong
ABSTRACT: The current work was intended to explore the function and mechanism of Kinesin family member 2C (KIF2C) in hepatocellular carcinoma (HCC). In this study, KIF2C expression was at a high level in HCC and indicated poor prognosis. Silencing KIF2C significantly suppressed the proliferation, migration, and invasion in HCC cells. Furthermore, silencing KIF2C markedly decreased the expression of Snail, Vimentin, p-MEK, and p-ERK, but increased E-cadherin expression in HCC cells. Moreover, we also found that MEK/ERK inhibitor U0126 could enhance the impact on cell proliferation, migration, and invasion induced by silencing KIF2C in HCC. On the contrary, MEK/ERK activator PAF could weaken the impact induced by silencing KIF2C in HCC. Thus, our findings indicate that KIF2C can promote the proliferation, migration, and invasion by activating MEK/ERK pathway in HCC. Graphical Abstract: